Sustainable Development of Hydropower through Integration of Floating Solar PV and Hydrokinetic Energy Systems - Singh, Ashutosh; Chelliah, Thanga Raj (Conference record of the Industry Applications Conference, 2025)
This research aims to explore innovative methods to improvise traditional hydropower systems by strategically integrating new forms of renewable energy resources. Two forms of renewable energy systems (RES) have been considered for the study which include floating solar PV (FSPV) system and hydrokinetic energy (HKE) system. Integration of FSPV arrays and hydrokinetic turbines with the hydropower infrastructure, the essential issue of improving clean energy generation and development of sustainable hydropower system can be achieved. In this study, assessment is carried out at the hydropower complex which comprises of peak load hydropower plant (HPP) and pumped storage plant (PSP) units to analyze the potential of harnessing wasted energy sources in the existing facilities. Considering the technology available, 264,696 MWh of energy can be generated by the FSPV system annually and diminishing evaporation losses from the reservoirs and improving solar cell efficiency, while a large scale of micro hydrokinetic system (50 KW each) can be installed at the specified site to capture untapped kinetic energy in tailrace channels, illustrating complementary display of operational synergies between different forms of RES and hydropower system. Continuous research focuses on mitigating technological limitations and the high cost of installation. For each technology, extensive study is carried out in terms of data analysis and case studies to estimate effective harnessing of renewable sources, which can be used for scaling up to large assessments.